A revision of the Afrotropical species of Hersilia Audouin (Araneae: Hersiliidae) - Foord, S. H.; Dippenaar-Schoeman, A. S. (Zootaxa, 2006)
This study revises the taxonomy of the most diverse genus in the family Hersiliidae, Hersilia, from the Afrotropical Region. Of the 22 previously known species, 16 species are redescribed and figured, two species synonymized: H. segregata Benoit with H. occidentalis Simon and H. nossibeensis Strand with H. insulana Strand, three species: H. kauderni Strand, H. stumpfi Strand and H. fossulata Strand are listed as nomina dubia and Hersilia corticola Lawrence is transferred to Neotama Baehr & Baehr. A neotype was designated for H. vinsoni Lucas. Hersiliopsis madagascariensis Wunderlich, previously only known from fossil amber, is transferred to Hersilia with the first description of the female. Fourteen new species are described and figured. Eight of these are described in both sexes: H. aldabrensis sp. n. from Aldabra Island Group and Comoros, H. bubi sp. n. from Equatorial Guinea and Uganda, H. furcata sp. n. from DR Congo, H. mboszi sp. n. from Cameroon, H. mowomogbe sp. n. from Cameroon, H. sagitta sp. n. from Kenya to South Africa, H. scrupulosa sp. n. from Kenya, H. selempoi sp. n. from Kenya, and four, H. caronae sp. n. from Ivory Coast, H. eloetsensis sp. n. from Madagascar, H. moheliensis sp. n. from Comoros, H. taita sp. n. from Kenya, and H. tamatavensis sp. n. from Madagascar are only known from males and H. igiti sp. n., from Rwanda, is only known from females. Five species groups are proposed for the 31 recognized species based on genital morphology: H. aldabrensis, H. baforti, H. caudata, H. savignyi and H. pectinata. Hersilia arborea Lawrence remains incertae cedis. Keys to these species groups and the 31 species are provided.